Randomized controlled trial comparing esophageal dilation to no dilation among adults with esophageal eosinophilia and dysphagia. Issue 8 (30th July 2015) - Kavitt, R. T.; Ates, F.; Slaughter, J. C.; Higginbotham, T.; Shepherd, B. D.; Sumner, E. L.; Vaezi, M. F.
Summary: The role of esophageal dilation in patients with esophageal eosinophilia with dysphagia remains unknown. The practice of dilation is currently based on center preferences and expert opinion. The aim of this study is to determine if, and to what extent, dysphagia improves in response to initial esophageal dilation followed by standard medical therapies. We conducted a randomized, blinded, controlled trial evaluating adult patients with dysphagia and newly diagnosed esophageal eosinophilia from 2008 to 2013. Patients were randomized to dilation or no dilation at time of endoscopy and blinded to dilation status. Endoscopic features were graded as major and minor. Subsequent to randomization and endoscopy, all patients received fluticasone and dexlansoprazole for 2 months. The primary study outcome was reduction in overall dysphagia score, assessed at 30 and 60 days post‐intervention. Patients with severe strictures (less than 7‐mm esophageal diameter) were excluded from the study. Thirty‐one patients were randomized and completed the protocol: 17 randomized to dilation and 14 to no dilation. Both groups were similar with regard to gender, age, eosinophil density, endoscopic score, and baseline dysphagia score. The population exhibited moderate to severe dysphagia and moderate esophageal stricturing at baseline. Overall, there was a significant ( P < 0.001) but similar reduction in mean dysphagia score at 30 and 60 days post‐randomization compared with baseline in both groups. No significant difference in dysphagia scores between treatment groups after 30 ( P = 0.93) or 60 ( P = 0.21) days post‐intervention was observed. Esophageal dilation did not result in additional improvement in dysphagia score compared with treatment with proton pump inhibitor and fluticasone alone. In patients with symptomatic esophageal eosinophilia without severe stricture, dilation does not appear to be a necessary initial treatment strategy.